Lovelight farms ebook - Borison, B.K (Lovelight, 2021)
One of Amazon's Best Romances of June! Two best friends fake date to reach their holiday happily ever after in this first romantic comedy in the Lovelight series. A pasture of dead trees. A hostile takeover of the Santa barn by a family of raccoons. And shipments that have mysteriously gone missing. Lovelight Farms is not the magical winter wonderland of Stella Bloom’s dreams. In an effort to save the Christmas tree farm she’s loved since she was a kid, Stella enters a contest with Instagram-famous influencer Evelyn St. James. With the added publicity and the $100,000 cash prize, Stella might just be able to save the farm from its financial woes. There’s just one problem. To make the farm seem like a romantic destination for the holidays, she lied on her application and said she owns Lovelight Farms with her boyfriend. Only…there is no boyfriend. Enter best friend Luka Peters. He just stopped by for some hot chocolate and somehow got a farm and a serious girlfriend in the process. But fake dating his best friend might be the best Christmas present he’s ever received.